Productions and Perceptions of Apologies: Intercultural Comparisons (Asian Education Studies, 2017)
The productions and perceptions of apologies vary from one language to another in terms of linguistic realization patterns, strategic preferences, and evaluative opinions. Accordingly, these variations motivate the investigation of apology use and its perceptions in different languages. By comparing productions and perceptions of apologies among college students who speak Arabic, Russian, English and Chinese languages, the current study reports on the students’ various strategic preferences (i.e., explicit or direct apology strategies, less explicit or indirect apology strategies and strategy combinations) and their diverging tendencies to evaluate the im/politeness of apologies. The results have confirmed that although the concept of apology is universal, its applications and interpretations can be divergent across various language groups and within each language group. These observed discrepancies can be attributed to sociocultural influences (e.g., face need concerns and culturally-specific perceptions of sincerity), gender-related differences (e.g., explicit and indirect apology strategies used more frequently by females than males) and situational characteristics (e.g., positive vs. negative face threatened situations, and in-group vs. out-group memberships). In addition, the author believes that this synthesis study will provide certain implications for ESL/EFL teaching and learning by enhancing the awareness of intercultural communicators to better make inferences from the effects of the three responsible factors on their use of apologies.